Demographic characteristics of teachers and their participation in faculty meetings - Lao, Bella M. 1932- (s.n.], 1967)
This study determined the demographic characteristics of teachers and their participation in faculty meetings in order to provide school administrators in the Division of Quezon City with data on the relationship of demographic characteristics of teachers and their participation in general faculty meetings and the reasons of teachers for assuming passive roles in these meetings. The purpose of the study is to promote the participation of teachers in the meetings so that they can contribute to the improvement of all aspects of the school and its educational program.